Possibilities for the use of hydroxychloroquine for pre- and postexposure prophylaxis of SARS-CoV-2 infection among exposed contacts and healthcare personnel - V. A. Otdelenov; A. V. Krykov; D. A. Sychev (Izdatelstvo OKI, 2020)
There currently exists no published robust data which would confirm effectiveness and safety of hydroxychloroquine in pre- and postexposure prophylaxis of SARS-CoV-2 infection. Taking into account in vitro data, which indicates inhibitory activity of hydroxychloroquine against SARS-CoV-2, and interim guidelines by the Ministry of Health of the Russian Federation, hydroxychloroquine can be considered as postexposure prophylaxis among healthcare personnel who have been in contact with patients with laboratory confirmed SARS-CoV-2, provided no contraindications and significant drug interactions are present. Safety monitoring should be performed before prescribing and during the course of treatment (ECG, total blood count and blood biochemistry, ophthalmologist evaluation before long-term treatment).